Hubungan antara pola pemberian makan dan pemberian ASI eksklusif dengan kejadian stunting tahun 2022 di Kelurahan Fatukbot, Nusa Tenggara Timur - Clara Maria Gabriela Keban; Cristina R. Nayoan; Mega O. L. Liufeto (Universitas Ahmad Dahlan, 2023)
Stunting is a condition where toddlers have a height that is less than the height of toddlers his age. The prevalence of stunting under five in East Nusa Tenggara (NTT) has decreased from 30% (2019) to 21% (2021). The purpose of this study was to determine the relationship between feeding patterns and exclusive breastfeeding with the incidence of stunting in Fatukbot Village, NTT. This study uses a Case Control method approach. The population in this study were stunted toddlers aged one to five years in the Fatukbot village, NTT. In this study, respondents recruited were 243 respondents where 81 respondents for case and 162 for the control groups. Control sampling used a variable matching method with LBW criteria, history of infectious diseases, maternal anemia and economic status. Feeding patterns were measured by collect information of food frequency and exclusive breastfeeding through questionnaires. The chi square test was employed for data analysis technique. The results showed that there was a significant association between feeding patterns and the incidence of stunting, X2 (1, N=243) = 0.21, p= 0.00. The results also showed that there was a significant association between exclusive breastfeeding and the incidence of stunting, X2 (1, N=243) = 0.29, p = 0.00, meaning that exclusive breastfeeding was a protective factor against stunting. Therefore, it is necessary to emphasize the importance of regular and good practice of feeding patterns and exclusive breastfeeding. Stunting could be reduced by implementing exclusive breastfeeding that is expected to be practiced until the babies aged 6 months and continue breastfeed until the age of 2 years. Food intake, variation and frequency eat in a day, should be monitored, at least, until under five years old.